Enhancing Student Skills through the Integration of Online Learning in Kenya's Competency-Based Curriculum (CBC) - Ndiangui, Peter; Mwangi, Francis Kamunya; Zhang, Jingshun (Research in Social Sciences and Technology- OpenED Network, 2025)
This study investigates the integration of online learning into Kenya's Competency-Based Curriculum (CBC), with the aim of improving educational access and equity. Although several educational reforms have been introduced in Kenya, challenges persist in fully implementing the CBC, including limited resources, technological gaps, and insufficient teacher training. The COVID-19 pandemic expedited the adoption of online learning, highlighting significant disparities in digital resource access between urban and rural areas. To evaluate the impact of online learning on student competencies, this research adopts a comparative approach, contrasting groups utilizing online tools with those relying on traditional teaching methods. The study employs cognitive diagnostic assessments to pinpoint specific areas of strength and weakness in students' knowledge and skills. In addition, concept mapping is utilized to visually organize and structure information, enhancing student understanding and retention. Findings from the study suggest that online learning can effectively increase student engagement, improve competency development, and provide more personalized learning experiences. To optimize the integration of online learning into the CBC framework, the study recommends key actions, including the enhancement of ICT infrastructure in rural schools to bridge the digital divide, the overhaul of teacher training programs to equip educators with digital pedagogical skills, and the implementation of inclusive policies ensuring equitable access to online resources for all students. Furthermore, the study encourages public-private partnerships to create tailored digital solutions addressing specific challenges in Kenya’s education system. These efforts could significantly enhance the CBC’s effectiveness, fostering more competent and skilled learners across the country.